History of Marshall Field & Co., 1852-1906 - Twyman, Robert W., 1919-2001 (Philadelphia : University of Pennsylvania Press, 1954)
This book is a volume in the Penn Press Anniversary Collection. To mark its 125th anniversary in 2015, the University of Pennsylvania Press rereleased more than 1,100 titles from Penn Press's distinguished backlist from 1899-1999 that had fallen out of print. Spanning an entire century, the Anniversary Collection offers peer-reviewed scholarship in a wide range of subject areas.
Frontmatter -- Preface -- CONTENTS -- ABOUT THE NOTES -- PLATES -- CHARTS -- TABLES -- NOTE BY THE PUBLISHER -- 1. Founding of the Firm -- 2. Marshall Field: Rising Young Merchant -- 3. The Man and the Opportunity -- 4. Field, Leiter and Company: Retail and Wholesale -- 5. Years of Trial -- 6. Years of Trial (Continued) -- 7. Personnel -- 8. New Hands at the Helm -- 9. New Hands at the Helm (Continued) -- 10. Customer Services -- 11. Advertising -- 12. The New and the Old -- Notes -- Bibliography -- Index.
Print version record.
Includes bibliographical references (pages 236-243) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: Marshall Field & Company; Field, Marshall, -- 1834-1906.; Field, Marshall, -- 1834-1906; Marshall Field & Company; BUSINESS & ECONOMICS / Industries / Retailing; Business; Economics